Makna Simbolik Kaulinan Barudak Oray-Orayan - Giyartini, Rosarina (PANGGUNG, 2014)
ABSTRACTÂ This research seeks to uncover the meaning behind the kids game Oray-orayan. The goal is that the values of local wisdom in it can be understood andapplied by a generation of people, especially people of West Java suit the demands of time so that the game can be sustainable. Assessmentmethods used for the benefit of the above hermeneutic within the framework of eï¬ective history and theory of fusion of horizons. Results ofthe study showed that the kids game Oray-orayan is symbolic form of the rite of purification throughbehavior back to theroom of origin. Thissymbolic wisdom can be brought into the present context as the source of the idea of creating art or dance lessons in primary school.Â Keywords: Oray-orayan, local wisdom, meaningÂ Â Â Â ABSTRAKÂ Penelitian ini berupaya menguak makna di balik permainan anak Oray-orayan. Tujuannya agar nilai-nilai kearifan lokal di dalamnya dapat dipahami dan diaplikasikan oleh generasi bangsa khususnya masyarakat Jawa Barat sesuai tuntutan jaman sehingga permainan tersebut dapat lestari. Metode kajian yang digunakan adalah hermeneutik dalam kerangka eï¬ective his- tory dan teori fusion of horizons. Hasil telaah menunjukkan bahwa permainan Oray-orayan adalah bentuk simbolik dari ritus penyucian melalui laku kembali ke ruang asal. Kearifan simbolik ini dapat dibawa ke konteks kekinian sebagai sumber gagasan penciptaan seni atau pembelajaran seni tari di Sekolah Dasar.Â Kata kunci: Oray-orayan, kearifan lokal, maknaÂ